2021
DOI: 10.1016/j.jcot.2021.02.007
|View full text |Cite|
|
Sign up to set email alerts
|

Charcot hindfoot deformity reconstruction using a hindfoot nail- surgical technique

Abstract: Various techniques of reconstruction of deformed Charcot hindfoot using different internal fixation devices have been described in the literature. We present our surgical technique using specific principles that has resulted in improved outcomes to allow correction of deformity, obtain stability and allow progression to weightbearing in orthotic shoes. We describe our preoperative evaluation, planning and surgical timing. We also hope to share some technical pearls and details on the finer points to achieve a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…An intact medial malleolus allows optimal positioning of the talus in the medial gutter corner, providing additional stability, particularly of the axial plane, and increases the surface area of bone contact. 10 We also demonstrated that talectomy did not affect the hindfoot union rates, although it did increase the risk of midfoot deformity recurrence. We feel that this is due to instability in the Charcot affected midfoot, as the navicular articulates with distal tibia anteriorly.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…An intact medial malleolus allows optimal positioning of the talus in the medial gutter corner, providing additional stability, particularly of the axial plane, and increases the surface area of bone contact. 10 We also demonstrated that talectomy did not affect the hindfoot union rates, although it did increase the risk of midfoot deformity recurrence. We feel that this is due to instability in the Charcot affected midfoot, as the navicular articulates with distal tibia anteriorly.…”
Section: Discussionmentioning
confidence: 58%
“…Additional screws and/or plates are often needed to improve the rigidity of the fixation construct. 10 We have found a union rate of 83%. Our union rates after hindfoot Charcot reconstruction are similar to those in the literature, 8,16 with overall fusion rates quoted at around 86%.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations